2021
DOI: 10.1186/s12978-021-01096-w
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of evidence-based practice and associated factors among nurses and midwives working in Amhara Region government hospitals: a cross-sectional study

Abstract: Background Implementation of evidence-based practice is crucial to enhance quality health care, professional development, and cost-effective health service. However, many factors influence the implementation of evidence-based practice. Therefore, this study aimed to assess the implementation of evidence-based practice and associated factors among nurses and midwives. Methods Institutional-based cross-sectional study design was conducted to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 32 publications
4
11
2
Order By: Relevance
“…However, this result was lower than that of Cable's study (42 ± 12 years) [16]. In contrast, the results of this study were higher than those of Asrat (28.35 ± 4.5 years old) [12]. Globally, the nursing workforce is relatively young, but there are regional disparities, with the age structure being essentially older than in the Americas and Europe regions [17].…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…However, this result was lower than that of Cable's study (42 ± 12 years) [16]. In contrast, the results of this study were higher than those of Asrat (28.35 ± 4.5 years old) [12]. Globally, the nursing workforce is relatively young, but there are regional disparities, with the age structure being essentially older than in the Americas and Europe regions [17].…”
Section: Discussioncontrasting
confidence: 73%
“…The implementation of EBP is critical to improving the quality of healthcare, professional development, and costeffective health services [12]. In addition, EBP is one of the key elements of nursing professional accountability.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence‐based practice implementation by nurses, the largest constituency of healthcare professionals, has become essential (World Health Organization/Europe, 2017). Numerous studies have shown that personal factors, like attitudes toward EBP, the knowledge and skills of EBP, educational level, participation in EBP education, and qualifications of advanced practice nurses, as well as work‐environment factors, like resources, organizational support for EBP, and time, are associated with nurses' EBP implementation (Dagne et al, 2021; Farokhzadian et al, 2015; Ominyi & Agom, 2020; Skela‐Savič et al, 2016; Tomotaki et al, 2020). Therefore, promoting EBP among nurses by focusing on the factors important to nurses' EBP implementation will be a crucial challenge over the coming decade.…”
Section: Introductionmentioning
confidence: 99%
“…The study found no association between research utilization and nurses' demographic factors. Conflicting results were found in some studies during the same Covid-19 Pandemic period iterating statistical association of research utilization to age, attitude to EBP and knowledge (pertaining to educational preparation) according to Dagne et al [18] study. Other factors or variables were identified as well as associated like civil status, and work experience (e.g., referring to number of years in the practice) afforded by the study done by Aynalem et al [20].…”
Section: Discussionmentioning
confidence: 93%
“…Attitude-wise, nurse practitioners that participated had that highest belief research is "stimulating, and interesting, and that it helped them professionally" to quote that very words used in the data gathering tool. It surely was a positive appreciation and research utilization attitude by the respondents as can be observed even during the very upsurge of Covid-19 Pandemic where there was as well an upsurge of publication and research studies [18]. It was even emphasized that research utilization during the pandemic period was significantly influenced by the nurses' competency and beliefs or as positive attitude [19].…”
Section: Discussionmentioning
confidence: 94%